2017
DOI: 10.4314/ecajs.v22i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an accelerated Ponseti protocol for the treatment of talipesequinovarus in Nigeria

Abstract: Background: The commonest congenital musculoskeletal deformity worldwide is talipes equino varus (CTEV). Of the various treatment methods available, the most acceptable treatment currently for CTEV worldwide is serial manipulation and casting using the Ponseti technique. The Ponseti technique consists of weekly manipulation and casting for an average of six to eight weeks followed by bracing of the feet till school age. Some studies have shown evidence that more frequent casts may have similar outcomes with we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Three studies were classified as having a low risk of bias [ 2 , 11 , 15 ]. The other six were classified as having a high risk of bias [ 9 , 10 , 16 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were classified as having a low risk of bias [ 2 , 11 , 15 ]. The other six were classified as having a high risk of bias [ 9 , 10 , 16 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of a shorter treatment duration is for the caregivers of the patients. Especially caregivers in low-income countries with limited access to healthcare centers are likely to benefit from a shortened casting period [ 2 , 11 , 16 , 23 ]. Other authors suggest that benefits of a shorter treatment are the reduced risk of skin problems, cast slipping and osteopenia [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the eligible studies are presented in Table 2 and include children from one day old [ 21 ] to 10 years [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Change in the mean Dimeglio score was evaluated in one study [ 25 ] and frequency of initial severity was reported with the Harrold-Walker classification in two studies [ 26 , 27 ]. Other definitions of primary outcome included: the number of days in casts [ 21 ], number of patients treated without extensive surgery [ 25 ], a plantigrade foot [ 24 , 28 , 29 ], no residual deformity [ 30 ], deformity status compared to previous visits [ 31 ] and parent reported outcomes on impact of treatment [ 32 ]. Limited definition terms included “complete correction” [ 26 ] and “satisfactory outcome” [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation